Lamps and lighting - Coaton, J. R.; Marsden, A. M. (Alfred Michael) (Routledge, 2012)
This book is a comprehensive guide to the theory and practice of lighting. Covering the physics of light production, light sources, circuits and a wide variety of lighting applications, it is both suitable as a detailed textbook and as thoroughly practical guide for practising lighting engineers. This fourth edition of Lamps and Lighting has been completely updated with new chapters on the latest lamp technology and applications. The editors ahve called upon a wide range of expertise and as a result many sections have been broadened to include both European and US practice. The book begins with a description of the fundamentals of light, vision, colour and measurement. Part II, the main section of the book, deals with lamps and control equipment and includes descriptions of all lamp types in use today. Part III on lighting covers both interior and exterior applications.